Exploring the role of Transactive Memory Systems in virtual teams: Review and synthesis of literature - Imran, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Although virtual teams are increasingly common in organizations, research on the formation of Transactive Memory Systems (TMS) in virtual teams and its effect on team performance is relatively rare. Previous studies have reported that TMS quality influences team performance in face-to-face teams. However, the effect of TMS quality on the performance of virtual teams has not been adequately researched in past studies. This paper systematically reviews and syntheses previous literature on TMS, virtual teams and team performance towards providing with a better comprehension explanation on TMS formation process that affects virtual teams performance. Â© 2015 IEEE.